FAKTOR-FAKTOR YANG MEMPENGARUHI HARGA SAHAM PERUSAHAAN TEKSTIL DAN GARMEN DI BURSA EFEK INDONESIA - Mira Kartika; Muhammad Tahwin (Sekolah Tinggi Ilmu Ekonomi YPPI Rembang, 2020)
The research aims to prove and analyze the influence of current ratio, return on asset, debt to equity and earning per share towards share prices in textile and garment company listed in Indonesia Stock Exchange. The population of the research is textile and garment factories listed in Indonesia Stock Exchange in 2013 – 2017 periods. Technique selection sample used is purposive sample. Data analyzes method used is multiple linier regression analyzes. The research result shows that current ratio has insignificant negative effect towards share price. Return to asset ratio has insignificant positive effect towards share price. Debt to equity ratio has significant negative effect towards share price. Earning per share has significant positive effect towards share price. Determination test result shows that variable current ratio, return on asset, debt to equity and earning to share are able to explain of 63,1% share price, while 36,9% of the remaining is explained by other factors that are not included in this research model.